Long-term biogas slurry fertilization alters rhizosphere soil metabolite profiles and microbial communities in poplar plantations - Gao, Xiao-Xiao; Yu, Xing-Ye; Jin, Chun-Zhi; Jin, Long; Bu, Su; Li, Taihua; Ruan, Hong-Hua; Shin, Kee-Sun; Jin, Feng-Jie (Frontiers in Microbiology, 2026)
Biogas slurry, a nutrient-rich organic fertilizer, has unclear impacts on plant-soil interactions. Rhizosphere metabolites serve as a bridge between plants and soil microorganisms, significantly influencing soil health and microbial activity. This study employed high-throughput sequencing and untargeted metabolomics to investigate microbial community and metabolite profiles in rhizosphere soil of poplar plantations treated with biogas slurry at different concentrations (Con: untreated; Low: 250 m3 ha−1 yr−1; High: 375 m3 ha−1 yr−1). Results showed that long-term application of biogas slurry significantly increased soil total nitrogen (TN) and available phosphorus (AP) levels, thereby enhancing soil fertility. Compared to fungi, biogas slurry treatment had a greater effect on bacterial community richness. Biogas slurry application also resulted in a significant decrease in organic acid content and a significant increase in nucleosides and nucleotides, saccharides, and esters in rhizosphere soil metabolites. Furthermore, differential metabolites between treatment groups were mainly classified into organic acids, organic bases, nucleosides and nucleotides, among others. Redundancy analysis (RDA) revealed that organic acids were positively correlated with NO3−, alkaline phosphatase (ALP) and pH, but negatively with TN and AP. KEGG pathway enrichment analysis revealed that in the Low vs. Con comparison group, differential metabolites were primarily enriched in amino acid metabolism, lipid metabolism, carbohydrate metabolism, and nucleic acid metabolism pathways. Co-occurrence networks indicated that the bacteria-soil properties-metabolites network was more complex than the fungal network. Our results suggest that low-concentration biogas slurry exerts stronger regulatory effect on rhizosphere metabolites and recruits beneficial microorganisms more effectively, with a lower ecological risk such as plant diseases.